An Error Analysis in Recount Text Written by The First Year of English Department Al-Qolam Islamic Institute Gondanglegi Malang: Qualitative Research - Budik Kusworo (Darussalam English Journal (DEJ), 2022)
Language is studied in Linguistics. In other words, linguistics is the scientific study of language. It has been mentioned by Lyons that Linguistics can be defined as the scientific study of Language. Error analysis is also studied in linguistics. It is used to determine someone's quality in using a second language or a foreign language. This study aims to analyze students' written text errors in Recount Text. This research is Research Analysis. The population is first-year students of the English Department at Al-Qolam Islamic Institute. There are 17 students. Student writing was analyzed using surface study taxonomy. The author found a total of 105 errors in student papers. It is also useful in everyday life, especially when giving public speeches. Because mistakes can be found not only in writing but also in conversation. Therefore, the writer suggests future writers utilize this research as an item to describe and compare the research topic with other theories because it will make a significant contribution to understanding errors.